Ventriculoperitoneal Shunt Treatment Increases 7 Alpha Hy-Droxy-3-Oxo-4-Cholestenoic Acid and 24-Hydroxycholesterol Concentrations in Idiopathic Normal Pressure Hydrocephalus - Emanuele Porru; Erik Edström; Lisa Arvidsson; Adrian Elmi-Terander; Alexander Fletcher-Sandersjöö; Anita Lövgren Sandblom; Magnus Hansson; Frida Duell; Ingemar Björkhem (Brain Sciences, 2022)
Idiopathic normal pressure hydrocephalus (iNPH) is the most common form of hydrocephalus in the adult population, and is often treated with cerebrospinal fluid (CSF) drainage using a ventriculoperitoneal (VP) shunt. Symptoms of iNPH include gait impairment, cognitive decline, and urinary incontinence. The pathophysiology behind the symptoms of iNPH is still unknown, and no reliable biomarkers have been established to date. The aim of this study was to investigate the possible use of the oxysterols as biomarkers in this disease. CSF levels of the oxysterols 24S- and 27-hydroxycholesterol, as well as the major metabolite of 27-hydroxycholesterol, 7 alpha hydroxy-3-oxo-4-cholestenoic acid (7HOCA), were measured in iNPH-patients before and after treatment with a VP-shunt. Corresponding measurements were also performed in healthy controls. VP-shunt treatment significantly increased the levels of 7HOCA and 24S-hydroxycholesterol in CSF (p = 0.014 and p = 0.037, respectively). The results are discussed in relation to the beneficial effects of VP-shunt treatment. Furthermore, the possibility that CSF drainage may reduce an inhibitory effect of transiently increased pressure on the metabolic capacity of neuronal cells in the brain is discussed. This capacity includes the elimination of cholesterol by the 24S-hydroxylase mechanisms.